Tyazhkiye nynche u NATO dela: chernogo lunsa otmyt' dobela - Kukryniksy (Плакат СССР (Plakat), 1981)
USA general scrubbing Swastikas off a dog-like Joseph Luns with NATO collar Original title: Тяжкие нынче у НАТО дела: черного лунса отмыть добела PO-0332